2015
DOI: 10.1136/jech-2015-205673
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing educational differences in mortality over 40 years: evidence from the Turin Longitudinal Study (Italy)

Abstract: BackgroundRecent studies suggest that inequalities in premature mortality have continued to rise over the last decade in most European countries, but not in southern European countries.MethodsIn this study, we assess long-term trends (1971–2011) in absolute and relative educational inequalities in all-cause and cause-specific mortality in the Turin Longitudinal Study (Turin, Italy), a record-linkage study including all individuals resident in Turin in the 1971, 1981, 1991 and 2001 censuses, and aged 30–99 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Data was drawn from the Turin Longitudinal Study (TLS), which is based on the city’s historical population registry from 1971 to the present. Demographic information from the registry is individually linked to census variables and routinely registered health events [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data was drawn from the Turin Longitudinal Study (TLS), which is based on the city’s historical population registry from 1971 to the present. Demographic information from the registry is individually linked to census variables and routinely registered health events [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have also evaluated secular trends in educational inequalities in CVD. In a 2015 study with over two million individuals in Italy, Stringhini et al showed that absolute inequalities for CVD mortality decreased substantially among men and women between 1971 and 2011 [68]. The aforementioned nationwide study from Norway showed that relative inequalities in acute myocardial infarction mortality remained constant between 2001 and 2009 (RII = 2.10, 2.06 to 2.15), although incidence decreased across all educational levels [66].…”
Section: Review Of the Evidence Education And Cvdmentioning
confidence: 98%
“…22 In Turin (Italy), socioeconomic disparities in CVD mortality declined substantially among men; no such notable reduction was seen for IHD inequalities, which indicates the presence of CVD-specific factors, for example, alcohol consumption. The decline in educational disparities in alcohol-related mortality in Turin over time coupled with the finding of higher alcohol consumption among high educated men 23 points to the role of changing patterns of alcohol intake in narrowing CVD inequalities.…”
Section: How Might This Impact On the Clinical Practice?mentioning
confidence: 99%